Evaluation of financial statements of sports clubs for 2019 and 2020 operational periods in terms of the COVID-19 pandemic and research in terms of financial risk - Sevim, A. (Journal of Corporate Governance, Insurance and Risk Management, 2021)
The Covid-19 pandemic and the accompanying uncertainties deeply affected the activities and financial structures of businesses and caused negative effects on their financial statements in many respects. Sports clubs are at the top of the list of businesses that suffer the most from the negativities of the pandemic process and experience a lot of loss in their financial and operational activities. Considering the developments both in Europe and in the World, the temporary postponement of sports matches, the start of competitions without spectators, the restructuring of club debts have seriously affected sports clubs, which are currently experiencing economic difficulties, deteriorate their liquidity, cash flows and increase uncertainty by making debt payments difficult. In addition, as the impact of risks on future performance increases, risk management practices have gained importance. In this context, information on the current ratio, cash ratio, financial leverage ratio, financing ratio, debt / equity ratio, and financial risk ratio obtained from the financial statement data for the period of 2019 and 2020 were used to evaluate the financial risk levels of 12 sports clubs. The deterioration in the financial structures of the sports clubs most affected by the pandemic process was examined and the risks encountered were discussed. In addition, the comparative financial analysis results were evaluated by analysing the effect of the financial structure and financial reporting of the clubs.